An individual-based modelling study estimating the impact of maternity service delivery on health in Malawi - Joseph H. Collins; Helen Allott; Wingston Ng’ambi; Ines Li Lin; Mosè Giordano; Matthew M. Graham; Eva Janoušková; Fannie Kachale; Kondwani Kawaza; Tara D. Mangal; Joseph Mfutso-Bengo; Emmanuel Mnjowe; et al. (Nature Communications)
Abstract Maternal and perinatal morbidity and mortality remain high in Malawi, partially due to gaps in the coverage and quality of health services. We developed an individual-based model of maternal and perinatal health and healthcare in Malawi, situated in a ‘whole-health system, all-disease’ framework (Thanzi La Onse). We modelled sixteen scenarios estimating the impact of current and improved coverage and quality of antenatal, intrapartum, and postnatal services from 2023 to 2030. Whilst current service delivery is inferred to avert morbidity and mortality, the largest reductions in the stillbirth, maternal and neonatal mortality rates were observed when the use and quality of all services was maximised concurrently (a 10%, 52% and 57% reduction respectively). When services were considered in isolation, generally, increased coverage without quality improvement did not impact mortality or DALYs. In only three scenarios was a sufficient reduction in neonatal mortality observed to achieve target 3.2 of the United Nation’s Sustainable Development Goals (SDG), and in no scenarios was a reduction in maternal mortality sufficient to achieve SDG target 3.1 observed, reaffirming that system wide investments are essential to achieve these goals.